2006
DOI: 10.1523/jneurosci.1595-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activation of mGlu4 Metabotropic Glutamate Receptors Reduces Nigrostriatal Degeneration in Mice Treated with 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine

Abstract: We examined whether selective activation of mGlu4 metabotropic glutamate receptors attenuates 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal damage in mice. C57BL mice were treated with a single dose of MPTP (30 mg/kg, i.p.) preceded, 30 min earlier, by a systemic injection of the mGlu4 receptor enhancer N-phenyl-7-(hydroxyimino)cyclopropa[b]chromen-1a-carboxamide (PHCCC). PHCCC was injected either subcutaneously in cremophor EL or intraperitoneally in saline containing 50% DMSO. PHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 32 publications
5
82
0
Order By: Relevance
“…havioral effects. Previous in vitro and ex vivo studies reported that a selective mGluR4 agonist induces neuroprotection against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity (Battaglia et al, 2006) and potentiates L-AP4-induced inhibition at striatopallidal synapse, whereas the mGluR8 agonist DCPG had no effect Valenti et al, 2003). In line with this, our results favor mGluR4-mediated effects at GP level because DCPG did not reverse haloperidol-induced catalepsy.…”
Section: Group III Mglurs Activation In the Globus Pallidus Produces supporting
confidence: 88%
“…havioral effects. Previous in vitro and ex vivo studies reported that a selective mGluR4 agonist induces neuroprotection against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity (Battaglia et al, 2006) and potentiates L-AP4-induced inhibition at striatopallidal synapse, whereas the mGluR8 agonist DCPG had no effect Valenti et al, 2003). In line with this, our results favor mGluR4-mediated effects at GP level because DCPG did not reverse haloperidol-induced catalepsy.…”
Section: Group III Mglurs Activation In the Globus Pallidus Produces supporting
confidence: 88%
“…This is interesting since the use of direct mGluR agonists like L-AP4 as a chronic treatment for PD is likely to be limited by adverse effects associated with excessive activation of the receptor, including receptor desensitization and loss of the neuronal activity dependence of receptor activation by pulsatile release of neurotransmitter (Conn, 2003). In conclusion, the findings presented herein, together with complementary data published during the course of the present study suggesting that the mGluR4-selective positive allosteric modulator PHCCC is neuroprotective against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced nigrostriatal damage in mice (Battaglia et al, 2006), provide compelling evidence that selective activation of Group III mGluR is neuroprotective in vivo in experimental models of parkinsonism, which may have implications for the future treatment of PD. …”
Section: Discussionsupporting
confidence: 71%
“…The drug was either injected systemically (5 mg/kg, s.c.) or infused intracranially in the cerebellar region (10 nmol/0.5 l). We expect that subcutaneously injected PHCCC at doses of 5 mg/kg can penetrate the brain because it can reverse reserpine-induced bradykinesia in mice (Battaglia et al, 2006). Control Ptc neo67/ϩ mice treated subcutaneously or intracranially with vehicle during the first 8 d of life showed the expected incidence of medulloblastomas (85-90%) when autopsied after 10 weeks (Fig.…”
Section: Activation Of Mglu4 Receptors With Phccc Inhibits Medulloblamentioning
confidence: 95%